Penerapan Metode Supervisi Dalam Meningkatkan Kualitas Proses Belajar Mengajar di SD Negeri 017 Pelambaian - Hartono, Sugeng (Komunitas Manajemen Kompetitif, 2017)
Problems that occur in SD N 017 Pelambaian, where the quality of teaching and learning problems in schools to be very less get the attention of the teachers as educators. The supervision carried out so far is still not optimal so that the implementation in the field becomes very apprehensive. The use of school action research methods resulted in the quality of teaching and learning of teachers assessed by the application of supervision methods to improve the quality of teaching and learning of teachers in teaching in schools. Keywords: Method of supervision, quality of teaching and learning process